Developing Students’ Skill in Writing Procedure Text Using YouTube Videos - Noeris Meiristiani; Nastasia Agistina (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
The purpose of this study is to determine whether YouTube videos are effective to use in teaching writing procedure text during the online learning process. It is experimental research with the population of all students of Class XI TMI in the first semester of SMK YPT Tegal in the academic year 2020/2021 with a total of 327 students. The sample was 40 students taken by using the cluster random sampling technique. The samples were grouped into two; (1) control group consisting of 20 students who were not taught using YouTube videos, and (2) experimental group consisting of 20 students who were taught using YouTube videos. The data analyzed using SPSS version 22 obtained the average post-test results of the two groups 78.50> 64.50. Based on the results of hypothesis testing using an independent sample t-test, a significance value of 0.000 was obtained, which was smaller than the significant value of a, which was 0.05, meaning that Ha was accepted. This means that there is a significant difference between the experimental group and the control group. In conclusion, the use of YouTube videos in teaching writing has a positive effect on the students’ writing skill.